The benefits of community-based participatory arts activities for people living with dementia: a thematic scoping review. Issue 3 (2nd September 2021) - Ward, Meghánn Catherine; Milligan, Christine; Rose, Emma; Elliott, Mary; Wainwright, Bethany Rebecca
ABSTRACT: Background: The drive towards living well with dementia has resulted in a growing recognition of the value of community-based participatory arts activities. This review aimed to explore their overall impact and holistic benefits for people with early to moderate stages of dementia. Methods: Using a scoping review methodology and thematic analysis, this review explored relevant literature published between 2008 and 2019. Results: 26 published papers were identified, comprising visual arts, literary arts, comedy, music and dance. The key themes included person-centred, in-the-moment approaches; participation and communication; attention and cognition; social cohesion and relationships; and the role of space, place and objects. Conclusions: There is strong evidence in support of using participatory arts for dementia, regardless of art form. In-the-moment and person-centred approaches were deemed impactful. Further research is needed to explore the importance of setting, material culture and the methodological or theoretical perspectives in participatory arts and dementia research.